Comportamento elétrico de nanocompósitos baseados em copolímeros em bloco e nanotubos de carbono - Santos, João Paulo Ferreira (2017)
In this work conductive polymer nanocomposites (CPNs) based on block copolymers and multi walled carbon nanotubes (MWCNT) were obtained. Two of the copolymers were commercial: polystyrene-b-polybutadiene-b-polystyrene (SBS), and polystyrene-b-poly(ethylene-butylene)-b-polystyrene (SEBS). The other copolymer was synthesized: polystyrene-b-poly(vinylidene fluoride) (PS-b-PVDF). Three systems of block copolymer/MWCNT were then obtained and studied for specific purposes. The SBS/MWCNT was produced using two routes: the solution and melt mixing. The influence of the processing conditions on the structure and on the electrical conductivity of these nanocomposites were evaluated and compared. For the second system, SEBS/MWCNT, the aim was evaluate the influence of the grafting of MWCNT with PS on the conductivity of the nanocomposites. For the third system, PS-b-PVDF/MWCNT, the aim was to evaluate the influence of the polymer matrix on the conductivity of the nanocomposites. The nanocomposites had their electrical properties evaluated by measurements of DC electrical conductivity and AC impedance spectroscopy. Their morphologies were evaluated by atomic force microscopy (AFM) and electron microscopy; and their structures were analyzed by small angle X ray scattering (SAXS). The results showed that the higher electrical conductivities and the lower percolation thresholds were obtained for the SBS/MWCNT nanocomposites obtained by the solution technique. The SEBS/MWCNT nanocomposites with PS grafted on MWCNT had higher conductivity than the non-grafted systems. The nanocomposites PS-b-PVDF/MWCNT had also better conductivities than the PVDF/MWCNT. Therefore, it was shown that both the modification of the processing, as well as the filler and the matrix are suitable approaches to control the structures and the electrical conductivity of CPNs based on MWCNT and block copolymers.